The screening of visual impairment among preschool children in an urban population in Malaysia; The Kuching pediatric eye study: A cross sectional study - Mallika, Premsenthil; Rose, Manju; Asokumaran, Thanaraj; Syed Alwi, Syed Abdul Rahman; Tan Aik, Kah (BioMed Central, 2013)
Background: To screen for visual impairment in Malaysian preschool children. Methods. Visual screening was conducted in 400 preschool children aged 4 to 6 years. The screening involved two basic procedures; the distant visual acuity test using the Sheridan Gardiner chart and the depth perception test using the Langs stereoacuity test. Criteria for referral were a visual acuity of 6/12 or less in the better eye or a fail in the depth perception test. Results: The prevalence of visual impairment was 5% (95% confidence interval [CI] = 3.3, 7.6). Of the 400 preschool children screened, 20 of them failed the distant visual acuity test or the stereopsis test. Refractive errors were the most common cause of visual impairment (95%, 95% CI = 76.2, 98.8); myopic astigmatism was the commonest type of refractive error (63.2%, 95% CI = 40.8, 80.9). Conclusion: The study is a small but important step in the effort to understand the problem of visual impairment among our preschool children. Our study showed that it is feasible to measure distant visual acuity and stereopsis in this age group.